Pengaruh Pengalaman Kerja, Pengetahuan, Pendidikan, dan Kebijakan Pimpinan Terhadap Penerapan Akuntansi Zakat, Infak/Sedekah (PSAK 109) pada Badan Amil Zakat di Daerah/Kota Pontianak dan Kubu Raya Kalimantan Barat. - Rizkia Milatul Fachriyyah; Khristina Yunita; Angga Permadi Karpriana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study examines the influence of work experience, knowledge, education, and leadership policies on the implementation of PSAK 109 for Zakat, Infaq, and Sadaqah accounting at Zakat Management Bodies in Pontianak City and Kubu Raya Regency, West Kalimantan. Although PSAK 109 is essential for ensuring transparency and accountability in zakat fund management, its implementation remains suboptimal in practice. A quantitative survey was conducted by distributing questionnaires to zakat officers (amil) at BAZNAS and Zakat Collection Units. Using purposive sampling, the data were analyzed through validity, reliability, classical assumption tests, and multiple linear regression. The findings reveal that work experience, knowledge, and leadership policies significantly and positively affect PSAK 109 implementation, while education does not show a significant effect. Collectively, all variables have a significant influence. The study concludes that practical competence, technical understanding, and supportive internal policies are more crucial than formal education. Strengthening training and leadership policies is recommended to enhance accountability and transparency.